2020
DOI: 10.1186/s13007-020-0554-1
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian approach for analysis of time-to-event data in plant biology

Abstract: Background: Plants, like all living organisms, metamorphose their bodies during their lifetime. All the developmental and growth events in a plant's life are connected to specific points in time, be it seed germination, seedling emergence, the appearance of the first leaf, heading, flowering, fruit ripening, wilting, or death. The onset of automated phenotyping methods has brought an explosion of such time-to-event data. Unfortunately, it has not been matched by an explosion of adequate data analysis methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Lidar cameras, accessible at low-cost [48], could be used to access to night events. Also, Bayesian approaches [6], such as Gaussian processes, could be used to estimate the time for the possibly missing information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidar cameras, accessible at low-cost [48], could be used to access to night events. Also, Bayesian approaches [6], such as Gaussian processes, could be used to estimate the time for the possibly missing information.…”
Section: Discussionmentioning
confidence: 99%
“…At the seedling level where plants have simple architectures, such time-lapse imaging can be done from top view to provide an efficient solution for seedling vigor assessments and monitoring of seedling growth. While some statistical tools transferred from developmental biology exists to perform time-to-event analysis [6], a current bottleneck [7] lay in the automation of the image analysis. A recent revolution occurred in the field of automated image analysis with deep neural networks [8], which have shown their universal capability to address almost any image processing challenges with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the authors demonstrated better results were obtained using the Bayesian statistical method relative to classical statistical analysis 33 . It is proposed that, accounting for the posterior distribution, this method properly deals with uncertainty, offering more realistic results 34 . Therefore, further investigation of the present data using different statistical models may reveal more insightful results.…”
Section: Discussionmentioning
confidence: 91%
“…[ 13 , 14 ]. As a high-throughput method, phenotyping produces a quantity of longitudinal or time-to-event data which is challenging to process by an adequate statistical approach [ 15 , 16 , 17 ]. In our study, we show that not considering the dependency that exists among individual time points in time series might lead to wrong assumptions, which might further cause a false hypothesis to be made.…”
Section: Introductionmentioning
confidence: 99%